The Use of Audio Visual Media on Learning Outcomes in the Merdeka Curriculum - Nonisa, Amanda; Darsono, Darsono; Nafisah, Riza; Ana, Rizki (Indonesian Journal of Education and Mathematical Science, 2024)
Rapid advances in science and technology have had a major impact on education, especially with the introduction of the Merdeka Curriculum which integrates literacy, skills and technology. One of the proposed solution is the use of audiovisual learning media that uses sight and sound to present material more interestingly and effectively. The purpose of the study is to destermine the impact of using audiovisual media on learning outcomes in the context of the Merdeka Curriculum. The method use is a literature review that collects data from various sources such as books,journal articles,and the internet. The data is analyzed descriptively to destermine the effectivitas of audiovisual media in improving mathematics learning. The research shows that audiovisual media can improve student understanding and retention by presenting material visually and audibly, so that learning becomes more interactive and interesting.